The Influence Of Work Ethic On Employee Performance (Study At The Library And Archives Office Of Garut District) - Santanu, Tita Rachtawati (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2020)
The purpose of this research is to determine the influence of work ethic on employee performance at the Garut Regency Library and Archives Service. The type of research used in this research is quantitative with a descriptive method approach and an associative method. The population in this study was 43 people, with a total of employees of the Garut Regency Library and Archives Service. Data collection techniques and tools are interviews, questionnaires and literature studies. The data analysis technique used is in the form of statistical formulas in the form of validity tests, reliability tests, correlation coefficient tests, determination coefficient tests, and hypothesis coefficient tests. Based on the results of the correlation test, a result of 0.610 was obtained, which is in the "strong" interval. The determination test results obtained were 37.2%. The results of the hypothesis test, the tcount value (4.928) can be compared with the ttable value (0.05;df) or (0.05;43-2) of 1.683. In accordance with the t-count value t-table or 4.928 1.683 or the Sig value of 0.000 is smaller than Alpha 0.05 then: H0 is rejected and H1 is accepted. It can be concluded that work ethic has a positive and significant effect.